Forging the Enemy: Fakeness, Invective, and Politics in the Panegyrici Latini and the Historia Augusta. - Bua, Giuseppe La (Illinois Classical Studies)
The article focuses on the role of epideictic rhetoric in late antique literature, particularly how invective and fictional narratives were employed to shape political discourse and imperial propaganda. It discusses how orators and historians used praise and blame to construct the image of legitimate emperors while discrediting usurpers, often through exaggerated or fabricated accounts. The text highlights the manipulation of historical narratives in works like the Latin Panegyrics and the Historia Augusta, where fictional invective served to reinforce moral and political authority, particularly against figures like Gallienus and Maxentius. Ultimately, the article illustrates how fictionality and invective were intertwined as tools for political legitimacy and social cohesion in a time of crisis.